Knowledge, Attitude, and Practices Towards Lightning in Bangladesh - Rahman, Md. Mostafizur; Nabila, Irtifa Alam; Sakib, Mohammed Sadman; Silvia, Nusrat Jahan; Galib, Muhammad Abdullahil; Shobuj, Ifta Alam; Hasan, Lamia; Chisty, Musabber Ali; Rahman, Farzana; Alam, Edris; Islam, Abu Reza Md Towfiqul (Sustainability, 2022)
Despite the significant number of fatalities and injuries, there is currently a lack of data on public knowledge, attitudes, and practices regarding lightning in Bangladesh. This study aims to assess the public’s knowledge, attitude, and practices (KAP) towards lightning in the country. A total of 1641 individuals participated in an online KAP survey. Where appropriate, the Kruskal–Wallis or Mann–Whitney U test, Spearman’s rank correlation, and logistic regression models were performed. About 65% of the survey population reported frequent lightning; most (72.64%) did not receive any warning messages, and small proportions (22.12%) had lightning safety precautions. Individuals with numerous lightning experiences perceived considerably unsafe places against lightning compared to infrequent lightning experiences (p < 0.05). Respondents reported good knowledge (56.06%), positive attitudes (82.27%), and good preventive practices (72.33%). The logistic regression demonstrated that having good knowledge and positive attitudes can help people practice lightning safety. Females demonstrated better lightning attitudes and practices compared to males. In comparison to urban residents, rural residents had poor practices. In addition, individuals’ educational levels might also play a crucial role in preparing them for lightning. Overall, extensive lightning campaign activities combined with effective education are required for the behavioral changes in this lightning-vulnerable society.